Features of conflict regulation of labor relations in the private international law (on the example of Czech Republic) - Любашенко, Анастасія Олексіївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
The article is focused on the investigation and review of the law conflict regulation of labour relationships in the private international law and particularly in the sphere of labour law using the example of the of Czech Republic. The author analyses the nature of law, the theoretical and practical aspects of the questions, which appear during the normative law regulation of labour relationships complicated with foreign element